STUDI ANALISIS TENTANG HUKUM ADOPSI ANAK PERSPEKTIF KITAB AL-FATAWA KARYA SYAIKH MAHMUD SYALTUT DAN KOMPILASI HUKUM ISLAM (KHI) - Moh zainun Najib; Ach. Faisol; Dwi Ari Kurniawati (Jurnal Hikmatina, 2021)
This study aims to describe the concept of adopted child status from the perspective of the book of Al-Fatawa by Sheikh Mahmud Shaltut and its relevance to the context of Islamic law applicable in Indonesia (KHI). This type of research is library research with a qualitative approach. The primary data source used in this study is the book of Al-Fatawa by Sheikh Mahmud Shaltut. While the secondary data sources are books, books, journals, and books that are related to what the author is discussing. The data collection technique in this research is documentation. Then analyzed with content analysis techniques and contextual analysis. The findings of this study are that the adoption of children is sunnah or allowed, but it is not allowed if it is decided that the lineage is with the biological parents and the adopted child has the same position as the biological child of the adoptive parents. The status of an adopted child according to Shaykh Mahmud Shaltut and KHI is not to decide on lineage with his biological parents, the child's status is still a biological child for his biological parents. The legal impact of adopted children in the inheritance of Islamic law does not include heirs, as well as according to Sheikh Mahmud Shaltut in Kitab Al-Fatawa, as for the alternative in getting a share of the inheritance of the adoptive parents by way of a will. In the Indonesian context, Islamic law regarding the status of adopted children in the book al-Fatawa by Mahmud Shaltut has relevance to the Compilation of Islamic Law (KHI) located in Article 171 (h).